1994
DOI: 10.1007/bf00454734
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function after femoral shortening osteotomies at the subtrochanteric and mid-diaphyseal level

Abstract: Relative femoral shortening length at the subtrochanteric (ST) and mid-diaphyseal (MD) level was compared with isokinetic muscle strength more than 2 years postoperatively. For the ST level no upper limit for shortening length could be detected. For MD osteotomies the relative shortening length was negatively correlated to muscle strength. There was a significant difference at the MD level between those shortened more or less than 10%, indicating an upper limit of 10% of the femoral length for regaining normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
1
1
Order By: Relevance
“…Other authors have suggested that the effect on the hamstrings tends to be less. 18 In contrast to the study by Holm et al, 10 we found that after two years the quadriceps and hamstrings had recovered to within 93% and 96% of their pre-operative values respectively, a change that was not statistically significant. There are a number of reasons that may explain this difference.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Other authors have suggested that the effect on the hamstrings tends to be less. 18 In contrast to the study by Holm et al, 10 we found that after two years the quadriceps and hamstrings had recovered to within 93% and 96% of their pre-operative values respectively, a change that was not statistically significant. There are a number of reasons that may explain this difference.…”
Section: Discussioncontrasting
confidence: 96%
“…This concurs with other studies of muscle function after femoral shortening. 10,12,18 It is of interest that atrophy of the quadriceps was more pronounced than of the hamstrings and that recovery was slower, particularly as the rehabilitation protocols tend to place greater emphasis on strengthening the former. Muscle is known to waste more if it is splinted in a shortened position 19 which may explain this observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Me to da osteoto mii skra ca ją cej sko śnej sta bi li zo wa nej 3 śru ba mi ana li zo wa na przez Rusz kow skie go wią że się, w je go opi nii, ze zbyt dłu gim okre sem od cią ża nia koń czy ny (6 ty go dni gip su bio dro we go, czę ścio we ob cią ża nie po 12 ty go dniach, peł ne ob cią ża nie do pie ro po 19 tygo dniach) [6]. Nord slet ten i współ au to rzy w przypad ku oste oto mii ty pu "Z" sto so wa li peł ne ob cią żanie do pie ro po 4 mie sią cach [7]. Koł ban i Kró lew ski nie sto so wa li unie ru cho mie nia w gip sie, ale za kaz ob cią ża nia koń czy ny obej mo wał okres od 2 do 4 miesięcy (śred nia 3 mie sią ce) [8].…”
Section: Dys Ku Sjaunclassified
“…The method of oblique shortening osteotomy stabilised by 3 screws as analysed by Ruszkowski necessitates, in his opinion, a too long period of limb unloading (6 weeks in a hip plaster cast, with partial loading after 12 weeks and full loading only after 19 weeks) [6]. Nordsletten and others used full loading only after 4 months following a "Z" type osteotomy [7]. Kołban and Królewski did not use plaster immobilisation but weight-bearing was prohibited for 2-4 months (mean: 3 months) [8].…”
Section: Type Of Osteotomy Stabilisationmentioning
confidence: 99%